Applicaton of Collapsible Mud Crab with Escape Gap in Laboratory Scale - Adi Susanto; Ririn Irnawati (Jurnal Perikanan dan Kelautan, 2012)
Use environmentally unfriendly mud crab fishing technology threat sustainability.  Catching crab is more environmentally friendly can be done with the installation of escape gap in collapsible trap. Escape gap use to escape not economic mud crab.  This study aims to determine the shape and size of escape gap and more effective installation position for use on collapsible traps. The results showed that the rectangle escape gap with dimensions 60x36 mm can carry a mangrove crab with carapace width <70 mm. The installation position of the most effective escape gap is on the side under the funnel with crab escape frequency percentage of 53%. Keyword: fishing technology, collapsible trap, escape gap, mud crab